Testing of hydrostatic drive of cranes mechanisms - Grigorov, O. V.; Anishchenko, G. O.; Petrenko, N.; Strizhak, V. V.; Turchyn, O. V.; Strizhak, Marjana; Okun, A. O. (AGIR Publishing House, Bucharest, Romania, 2019)
At present, the experts of lifting, transport, construction and road equipment are tasked with significantly improving the productivity of loading and unloading operations, improving performance characteristics, increasing the durability and reliability of machines. One of the ways of solving these problems is the widespread use of hydraulic transmissions in various mechanisms of cranes, construction and road machines. The results of researches on the cranes (bridge, tower and portal) with hydrostatic drives of travel and slewing mechanisms are given. The results of testing are compared with the solutions on the computer. Recommendations for a significant increase hydrostatic drives limit number of fatigue cycles of welded joints of crane steel structures in relation to a drive with a phase rotor are given.
Keywords: damages; loads acting on cranes steel structure; hydrostatic drives; fatigue of crane units; oscillograms of tests